Brand Building of Retail Stores - S, Deepa; P, Chitramani (Journal of Contemporary Research in Management (JCRM), 2013)
The emerging organized retail sector of India puts forth many challenges for both the new entrants as well as the existing retailers, the retailers have to differentiate themselves from the competition to gain the customer trust and loyalty. Branding is considered as one of the important means in establishing and maintaining competitive advantage by most of the companies in various industries. Earlier the focus of the marketers was limited to the marketing mix elements to develop competitive edge over their counterparts. The paradigm shift in marketing emphasizes the importance of branding. The digital economy which initiated the transformation in retail by changing traditional geographic boundaries, and enabled customers to access the products and services through the digital media also offer both opportunities and challenges to the retailers in building brands. In this scenario establishing and communicating a brand may be harder for multibrand retailers than for their single-brand counterparts, but brand building is essential for both. The present study focuses on brand building strategies of the retail stores which fall under the hypermarket format in Coimbatore city. Case study method was adapted to discuss the brand building strategies of retailers in the city. The major retailers of the Coimbatore city were contacted with a set of questions to find out their initiatives in building their brands. Based on the findings this paper highlights the various brand building strategies need to be adopted in the retail industry.